Pengaruh Isi Pesan, Sumber Pesan, dan Insentif Pada Sikap Konsumen Terhadap Sms Advertising - Anggi Surya Saputra; Yenny Purwati (Conference In Business, Accounting, And Management (CBAM), 2012)
The rapid proliferation of mobile phones and other mobile devices has created a new channel for marketing. Mobile advertising has emerged as one of the most popular application in mobile commerce, particularly in the form of SMS advertising. This research investigates the influence of message content, message source, and incentive on consumer attitudes toward SMS advertising. An emprical method is used and three hypotheses are tested. Our findings confirmed the three hyphoteses. The analysis is based on a consumer survey. For this purpose a judgemental sampling of 200 cellular phones users in Semarang has been assesed. The results indicate (1) consumer give a great attention toward the entertainment aspect on message content which in further lead to positive attitudes toward sms advertising; (2) message source is the most important factor affecting consumer attitudes toward sms advertising; (3) incentives that offer monetary incentives such as pulse and free minutes lead to more positive attitudes to receive and read SMS advertisingKeywords: content, source, incentives, SMS advertising, attitude